Pengaruh Penerapan Total Quality Manajemen Pada Bagian Produksi Terhadap Kualitas Produk Dan Efisiensi Biaya Produksi - ., Marsha; ., Hastoni (Institut Bisnis dan Informatika Kesatuan, 2016)
Management plays key parts in running operations of a business chain. Management combined with human resources will determine the success of a company. Along the way, in the currently tight business competition, consumers demand improved product quality and affordable price at the same time. One of the many ways company can choose to establish this condition is by applying Total Quality Management. This research is purposed to examine whether or not there are differences in quality and cost efficiency before and after the application of quality management and how the quality management carried out. The results show that there are differences in the quality produced before and after the implementation of quality management. After the implementation, there is a decrease in the reject products and the production cost is lower. This concludes that the application of total quality management is beneficial for the company due to well manage communication and supervision among managers and operating staffs.